Cap-Independent Translation in Hematological Malignancies - Horvilleur, Emilie; Wilson, Lindsay A.; Bastide, Amandine; Piñeiro, David; Pöyry, Tuija A. A.; Willis, Anne E. (Frontiers in Oncology, 2015)
Haematological malignancies are a heterogeneous group of diseases deriving from blood cells progenitors. Although many genes involved in blood cancers contain Internal Ribosome Entry Sites (IRESes) there has been only few studies focusing on the role of cap-independent translation in leukaemia and lymphomas. Expression of IRES Trans Acting Factors (ITAFs) can also be altered and interestingly BCL-ABL1 fusion protein expressed from “Philadelphia” chromosome, found in some types of leukaemia, regulates several of them. A mechanism involving c-Myc IRES and cap-independent translation and leading to resistance to chemotherapy in multiple myeloma emphasize the contribution of cap-independent translation in blood cancers and the need for more work to be done to clarify the roles of known IRESs in pathology and response to chemotherapeutics.